2015
DOI: 10.3390/ijms160817456
|View full text |Cite
|
Sign up to set email alerts
|

A Single Nucleotide Polymorphism near the CYP17A1 Gene Is Associated with Left Ventricular Mass in Hypertensive Patients under Pharmacotherapy

Abstract: Cytochrome P450 17A1 (CYP17A1) catalyses the formation and metabolism of steroid hormones. They are involved in blood pressure (BP) regulation and in the pathogenesis of left ventricular hypertrophy. Therefore, altered function of CYP17A1 due to genetic variants may influence BP and left ventricular mass. Notably, genome wide association studies supported the role of this enzyme in BP control. Against this background, we investigated associations between single nucleotide polymorphisms (SNPs) in or nearby the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
0
7
0
4
Order By: Relevance
“…6-9 A recent study has also associated rs11191548 with left ventricular mass index (LVMI) in hypertensive patients, which is suggestive of a role in cardiac hypertrophy. 10 Rare genetic variants at CYP17A1 are already known to cause hypertension and so this locus represents a rare concurrence of blood pressure candidate gene studies with GWAS evidence.…”
Section: Introductionmentioning
confidence: 99%
“…6-9 A recent study has also associated rs11191548 with left ventricular mass index (LVMI) in hypertensive patients, which is suggestive of a role in cardiac hypertrophy. 10 Rare genetic variants at CYP17A1 are already known to cause hypertension and so this locus represents a rare concurrence of blood pressure candidate gene studies with GWAS evidence.…”
Section: Introductionmentioning
confidence: 99%
“…An associated study among European ancestry participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium indicated that polymorphism rs743572 was associated with BP traits [ 39 ]. Another recent study conducted in patients with arterial hypertension and cardiac left ventricular ejection fraction revealed that no significant association was found between SNP rs743572 and mean 24-h systolic or diastolic BP [ 40 ]. In our study, no association was observed between this polymorphism and EH among the Han Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…CYP17A1 encodes 17 α -hydroxylase which is essential to the synthesis of cortisol precursors. Therefore, alteration of this gene can cause a deficiency in 17 α -hydroxylase and thus cortisol, which affects blood pressure [ 57 ]. Supporting the role of CYP17A1 in blood pressure regulation is the SNP rs11191548, a SNP near the CYP17A1 gene that has been consistently associated with blood pressure in both East Asian cohorts and Caucasian cohorts [ 10 , 17 , 18 , 58 60 ].…”
Section: Biological Pathways Involved With Blood Pressure Pathophymentioning
confidence: 99%